Hadith #3965 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sharhbayl bin al-Samat; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Abi Dawud)
Along with the Messenger of Allah (ﷺ) we besieged the palace of at-Ta’if. The narrator, Mutadh, said: I heard my father (sometimes) say: “Palace of at-Ta’if,” and (sometimes) “Fort of at-Ta’if,” which are the same. I heard the Messenger of Allah (ﷺ) say: he who causes an arrow to hit its mark in Allah’s cause will have it counted as a degree for him (in Paradise). He then transmitted the rest of the tradition. I heard the Messenger of Allah (ﷺ) say: If a Muslim man emancipa
Grade: Sahih

Hadith #3966 - Sunan Abi Dawud - Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Sharhbayl bin al-Samat; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If anyone emancipates a Muslim slave, that will be his ransom from Jahannam.
Grade: Sahih